Өндөр гэгээн Занабазарын эх Ханджамц хатны удам гарлыг нягтлах нь - .Ц, Цэрэндорж (Acta Mongolica, 2018)
The opinion that Khandjamts hatan is a daughter of Dalai taish of Durbed tribe is widely accepted among the Mongolian scholars. However, this opinion is based only on the manuscript which called “The Biography of Undur gegeen”. There is no enough evidence because there are different records on the origin of Khandjamts hatan in historical sources such as the daughter of a daugther of a younger brother of Ochir Khan (Abatai Sain Khan) or the Queen of the King of Qarsiri. In this paper, we have tried to make clear the origin of Khandjamts khatan comparing the relating information in various historical sources, not only religious sources such as “The Biography of Undur gegeen” but also official chronicles written in Mongolian and Manchu languages.